Popularyzacja czytelnictwa oraz historii ojczystej w twórczości literackiej krakowskiej bajarki i animatorki kultury Marii Niklewiczowej - Uljasz, Adrian (Tematy i Konteksty, 2019)
Maria Niklewiczowa, an author of children’s literature, , contributed to the popularization of reading practice through telling her fairy tales during public shows and having her stories published later on, based on the idea that listening to fairy tales belongs to children’s first contacts with literature. As an author of novels, she promotedg the knowledge of history. She was an organizer of cultural activities as well, as evidenced in her fairy tale reading sessions. Until today, her most popular book is a volume of fairy-tales titled „Bajarka opowiada” (first edition – 1959).